A randomized phase 2 study of combination cediranib and olaparib versus olaparib alone as recurrence therapy in platinum-sensitive ovarian cancer - Liu, Joyce F. (Lancet Oncol, 2014)
BACKGROUND: Olaparib is an oral poly(ADP-ribose) polymerase inhibitor and cediranib is an oral anti-angiogenic with activity against VEGFR-1, 2, and 3. Both agents have antitumor activity in women with recurrent ovarian cancer, and the combination of these agents was active and had manageable toxicities in a Phase 1 trial. We asked whether the combination of cediranib and olaparib could improve progression-free survival compared to olaparib monotherapy in women with recurrent platinum-sensitive ovarian cancer. METHODS: We conducted a randomized, open-label, phase 2 study to evaluate the activity of olaparib monotherapy compared with combination cediranib and olaparib in women with ovarian cancer with measurable platinum-sensitive, relapsed, high-grade serous or endometrioid disease or those with deleterious germline BRCA1/2 mutations (gBRCAm). Patients were randomized using permuted blocks within stratum defined by gBRCA status and prior anti-angiogenic therapy to receive olaparib capsules 400mg twice daily or the combination at the recommended phase 2 dose of cediranib 30mg daily and olaparib capsules 200mg twice daily. The primary endpoint was progression-free survival (PFS) analyzed under intention to treat. The trial is registered with ClinicalTrials.gov, NCT01116648. The Phase 2 portion of the trial reported here is no longer accruing patients. FINDINGS: Forty-six of 90 randomized patients received olaparib alone, and 44 received cediranib/olaparib. Median PFS was significantly longer with cediranib/olaparib (17.7 vs. 9.0 mos, HR 0.42; p = 0.005). Grade 3 and 4 adverse events were more common with cediranib/olaparib, including fatigue (12 vs. 5), diarrhea (10 vs. 0), and hypertension (18 vs. 0). Subset analysis within stratum defined by BRCA1/2 status demonstrated activity of cediranib/olaparib in both gBRCAm and gBRCAwt/u (wild-type/unknown) patients. Significant improvement in PFS occurred in gBRCAwt/u women receiving cediranib/olaparib (16.5 vs. 5.7 mos, p = 0.008) with a smaller trend towards increased PFS in gBRCAm patients (19.4 vs. 16.5 mos, p = 0.16). INTERPRETATION: The combination of cediranib and olaparib significantly extended PFS by 8.7 months compared to olaparib alone in recurrent platinum-sensitive ovarian cancer. The activity observed with this oral combinaton in both gBRCAmt and gBRCAwt/u patients is encouraging and should be further explored as a potential alternative to cytotoxic chemotherapy. Given the side effect profile, such explorations should include assessments on quality of life and patient-reported outcomes to understand the effects of an ongoing oral regimen to that of intermittent chemotherapy.